High-tech services as an element of innovative economy development: identification features and defining characteristics - Sokolov, Aleksandr V.; Goraeva, Tatiana Yu. (Journal of the Belarusian State University. Economics, 2025)
The article analyses the high-tech sector of the economy and studies and classifies high-tech services as components of this sector. The article focuses on the issue of identifying high-tech and knowledge-intensive services. The main characteristics of high-tech services are presented, and their definition is provided. The article discusses the challenges of defining and statistically accounting for high-tech services in the Republic of Belarus and emphasises the need for further development of the theoretical and methodological framework for this sector.